An evaluation of the European’s Community’s "Convention on human rights and biomedicine" - Bompiani, Adriano (Medicina e Morale, 1997)
The article concerns the recent "Conventon on human rights and biomedicine" drawn up by the European Community's Bioethics Commission and approved by the Committee of European Ministers in November 1996. Since the approved text will be completed by protocols which explain the principles stated in the Convention, the author provides a brief history of the document and analyses the reasons why it was drafted, the general creteria adopted and the main ethical principles which inspired it. The analysis of the Convention attempts to answer the following questions: how should the Convention's contents be evaluated? Which ethical principles and criteria do the Convention's proposals correspond to? And finally, which aspects concern the obligations of the partecipating countries and the control mechanisms, and what are the reservations and interpretations of this international instrument? Briefly, the last part of the paper can be summarized as follows: 1. certain points in the text of the Convention are valuable (like the claim for the need to protect the human being, which remains a priority with respect to the interest of society) and others are questionable (like, for example, the protection of prenatal life, the assisted fertilization techniques, assistence for the dying, etc.); 2. the Convention goes back to the ethical principles of active, technological and experimental medicine, which are present in the English speaking world, described as "principlism"; 3. procedures which aim to guarantee the fulfilment of the contents of the Convention are established, although during ratification, the member countries can express reservations if a law in force in their country is not in conformity with the Convention's dispositions.